Factors explaining seasonal variation in energy intake: a review - Fujihira, Kyoko; Takahashi, Masaki; Wang, Chunyi; Hayashi, Naoyuki (Frontiers in Nutrition, 2023)
Maintaining a balance between energy intake and expenditure is crucial for overall health. There are seasonal variations in energy intake, with an increase during spring and winter as well as a decrease during summer. These variations are related to a combination of environmental factors, including changes in temperature and daylight hours; social factors, including events and holidays; and physiological factors, including changes in physiological activity and emotions. Accordingly, this review aimed to summarise the environmental, social, and physiological factors that contribute to seasonal variations in energy intake. A review of the current literature revealed that changes in temperature and daylight hours may affect eating behaviour by altering homeostatic responses and appetite-related hormones. Additionally, increased participation in events and frequency of eating out, especially during winter vacations, may contribute to increased energy intake. Notably, these findings may not be generalisable to all populations since environmental and social factors can vary significantly depending on the local climatic zones and cultural backgrounds. The findings of the present review indicate that seasonal climate, events, and associated hormonal changes should be taken into account in order to maintain adequate energy intake throughout the year.